The use of motivational interviews by nurses to promote health behaviors in adolescents: A scoping review protocol - Lomba, Maria de Lurdes Lopes de Freitas (2016)
Abstract The developmental changes during adolescence may affect subsequent risk for diseases and health-related behaviors. Traditionally, professionals assume that knowledge is sufficient for behavioral changes; however adolescents continue to engage in unhealthy behaviors despite clearly knowing what they should do and how to change. "What is lacking is the motivation to apply that knowledge". Motivational Interview (MI) may be taken as an essential tool in the provision of nursing care to adolescents, being itself a workspace with possible therapeutic effects. Objectives The objective of this scoping is to examine and map the use of MI by nurses in their clinical practice with adolescents to promote health behaviors. The review will focus on knowing what is the current extent of the use of nurse-led MI; which adolescent populations were included; in which contexts nurses use MI; which MI techniques/strategies have been used and what outcomes on health behaviors promotion have been reported. Methodology This scoping review will be informed by JBI methodology. The population of this study is adolescents aged 10 to 19 years participating in nurse-led MI. The concept of MI include MI done by personal or telephone call, with any number of sessions, brief interventions and other motivational interventions grounded but not limited to the principles described by Miller & Rollnick (2008). All geographical and all clinical practice contexts where nurses' undertake MI with adolescents such as hospitals, primary health care, health care centers, community or schools will be contemplated. English, Spanish and Portuguese published studies will be considered for inclusion. Results An initial limited search of MEDLINE and CINAHL was undertaken followed by analysis of the text words contained in the title and abstract, and of the index terms used to describe the concepts, synonyms (with truncations), MeSH Terms and Cinhal headings of this study. It was identified 5 synonyms for "Adolescents", 7 for "MI" and 2 for "nurse". A first search using the all 14 identified keywords and index terms was made at Medline (Title/Abstract) and brought up 125 articles. Other 16 databases referenced at the protocol will be searched to identify additional studies. Articles identified from the final search will be assessed for relevance to the review, based on information provided in the title and abstract. The full article will be retrieved for all studies that meet the inclusion criteria of the review. It is expected that findings from this Scoping Review provide needed information to nurses related to the use of MI to promote health behaviors in adolescents. Conclusions There is little knowledge of what works for whom (which adolescent subpopulation) under what circumstances (in which setting, for what problem) in relation to nurse-led MI. There is a need for scoping or mapping the nurse-led MI with adolescents to identify evidence gaps and to inform opportunities for future development in nursing practice. Moreover, information regarding implemented and evaluated interventions, techniques used, contexts of application and adolescents groups is dispersed in the literature which impedes the formulation of questions about the outcomes and effectiveness of those interventions. The practical implication of this mapping will be clarifying all these aspects.